Revealed distributional preferences: Individuals vs. teams - Loukas Balafoutas; Rudolf Kerschbamer; Martin Kocher; Matthias Sutter (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2013)
We compare experimentally the revealed distributional preferences of individuals and teams in allocation tasks. We find that teams are significantly more benevolent than individuals in the domain of disadvantageous inequality while the benevolence in the domain of advantageous inequality is similar across decision makers. A consequence for the frequency of preference types is that while a substantial fraction of individuals is classified as inequality averse, this type disappears completely in teams. Spiteful types are markedly more frequent among individuals than among teams. On the other hand, by far more teams than individuals are classified as efficiency lovers.
Keywords: C91; C92; D03; D63; D64; 330; Distributional Preferences; Social Preferences; Team Decisions; Individual Decisions; Stability of Preferences; Behavioral Economics; Experimental Economics; Offenbarte Präferenzen; Gruppenentscheidung; Verhaltensökonomik; Experimentelle Ökonomik